BANGTAN SONYEONDAN (BTS) AS NEW AMERICAN IDOL - Ade Nine Suryani (Universitas Gadjah Mada, 2019)
South Korean pop songs or colloquially K-pop has spread globally. America also has a massive impact on this K-pop wave phenomenon. America now gives its enormous attention to the Bangtan Sonyeondan group or BTS group because this K-pop group is prevalent and becomes the new idol in America. In the beginning, K-pop is not successful, but until BTS comes and becomes a global sensation there. This paper tries to analyze which factors enable BTS to be the new idol in America. The writer uses a qualitative method to conduct the data and reception theory from Stuart Hall in the analysis. This analysis results in BTS, as the most popular K-pop group in America nowadays, has two factors that enable them to dominate American fans. The first one is through their androgyny physical appearance that redefines American traditional macho masculinity. The second one is through messages in their songs that raise social issues and mental health problems, helping their fans survive in their harsh lives.Keywords: BTS; decoded; encoded; k-pop; reception theory